2019
DOI: 10.1259/bjr.20190455
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic utility of serial 18F-FDG-PET/CT in patients with locally advanced rectal cancer who underwent tri-modality treatment

Abstract: Objective: This study explored the value of serial 18-fludeoxyglucose-positron emission tomography (18F-FDG-PET/CT) in predicting disease-free survival (DFS) in locally advanced rectal cancer (LARC) treated with neoadjuvant chemoradiation (NCRT) and surgery. Methods: We prospectively studied 46 patients with LARC who underwent NCRT and surgery. 18F-FDG-PET/CT scans were performed at three time-points before surgery (pre-NCRT-PET1, during NCRT-PET2 and following completion of NCRT-PET3). The following semi-quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
4
1
Order By: Relevance
“…In this study, we found that post-TLG had a negative predictive value of 92.59% for GR status in LARC patients, but did not show a predictive advantage in pCR status. In previous studies, there have been meaningful reports about MTV, DMTV and DTLG in predicting the responsiveness of LARC patients to nCRT (8,(25)(26)(27). However, in our study, none of these three parameters was found to have meaningful predictive value in our study.…”
Section: Discussioncontrasting
confidence: 89%
“…In this study, we found that post-TLG had a negative predictive value of 92.59% for GR status in LARC patients, but did not show a predictive advantage in pCR status. In previous studies, there have been meaningful reports about MTV, DMTV and DTLG in predicting the responsiveness of LARC patients to nCRT (8,(25)(26)(27). However, in our study, none of these three parameters was found to have meaningful predictive value in our study.…”
Section: Discussioncontrasting
confidence: 89%
“…The metabolic tumor volume (MTV) was defined as the hypermetabolic tissue volume with a threshold of 42% of the SUVmax ( 19 ). The total lesion glycolysis (TLG) was calculated according to the formula: TLG = SUVmean × MTV ( 20 ). For the ADC measurement, the region of interest (ROI) was drawn manually along the edge of the largest tumor area section on the DWI image with a b-value of 800 s/mm 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Only 25 patients (76%) had DCE MRI after CRT. Although the study did not formally collect information on reasons why patients declined MRI during and after CRT, a commonly cited reason was that patients wanted to focus on treatment and surgery, and did not want to undergo extra trial investigations, which in this study included MRI, positron emission tomography [33] and circulating tumour cells at three timepoints. Despite the small sample size, we found that DCE MRI after CRT was statistically significant for predicting DFS.…”
Section: Discussionmentioning
confidence: 99%